URBAN IDENTITY: CULTURAL-PHILOSOPHICAL ANALYSIS - Kravchenko, Oksana (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2022)
Introduction. Examining the historical development of the city, we can see that, despite the seemingly all-encompassing nature of the Christian worldview, its social norms and standards are clearly manifested only in the urban environment. The aim and tasks are a cultural-philosophical study of the concept of "urban identity" and its relationship with the cultural code of the city. Research methods. The article uses cultural and philosophical analysis, the principle of historicism and socio-cultural approach. Research results. The city emerges as a unique social space in which an attempt is made to break the organic connection with natural processes, which remained the main feature of rural life, determining the way of thinking and values of the rural population. Unlike the rural man, who in eternal and inseparable connection with nature in his life is guid-ed by customary law, the rules of which are based on the principle of "so it was from age", citizens, separating themselves from the field and nature by an unshakable wall, create a republic. governed not by natural but by social laws. Discussion. The formation and historical development of urban space largely determines the cultural values and motives of human behav-ior in society. However, the heterogeneity of this process suggests the need to study the impact of urban space on the cul-tural identification of man in modern society. The very process of human perception of any cultural tradition is associated with the definition of the environment and the stages of its formation. Conclusion. Summarizing all above, we note that each city has its own identity and semantics, which were formed throughout the historical development of the city itself. They concentrate all culture, from architectural monuments, theaters, museums, theme parks, leisure facilities, and ending with modern art grounds, innovative works of art. Each city has its own traditions, its own coat of arms and even its own anthem. All this creates a unique code of the city, not inherent in any other city. The interaction of this system of images as a whole leads to the formation of the image of the city.